Japan's ODA assistance scheme and Central Asian engagement: Determinants, trends, expectations. Issue 1 (2016) - Dadabaev, Timur
As demonstrated in this paper, Japan over the years has grown to become the leading ODA provider in Central Asia (CA). ODA has served as a foreign policy tool and as the most significant tool for maintaining cooperation ties. Although the focus of Japan's ODA assistance over the years has been on East Asian countries, CA is growing to become another frontier for more proactive Japanese policies. The Japan-supported initiatives of recent years tend to favor more pragmatic cooperation schemes. As is exemplified by water-related assistance in Uzbekistan and support for local capacity building in Kyrgyzstan, Japanese assistance of a more focused character can better contribute to development both in these societies and in the region in general. These types of initiatives can successfully complement government-to-government assistance schemes and Japanese investments into large scale projects. The focus on local communities will also ensure that beneficiaries of the Japanese assistance projects will include not only governmental institutions but also the general public at large.